The Arrangement - Modglin, Kiersten ([United States?] : [Publisher not identified], 2021)
When Ainsley Greenburg realizes her marriage is at its breaking point, she devises a plan to repair it, no matter the cost. The rules are simple: they will each date someone new once a week, and they will never discuss what happens on the dates. Her husband, Peter, agrees almost immediately. Soon the rules are broken, with terrible mistakes and unspeakable consequences.
Keywords: Adultery -- Fiction; Open marriage -- Fiction; Man-woman relationships -- Fiction; Marital conflict -- Fiction; Marriage -- Fiction; Secrecy -- Fiction; Truthfulness and falsehood -- Fiction; Psychological fiction; Thrillers (Fiction); Thrillers (Fiction); Psychological fiction